Tourism-Induced Place Change: The Role of Place Attachment, Emotions, and Tourism Concern in Predicting Supportive or Oppositional Behavioral Responses. (January 2022) - Lalicic, Lidija; Garaus, Marion
This study investigates residents' emotional and behavioral responses to environmental changes caused by tourism development. Statistical analysis conducted on a comprehensive sample of 1, 001 residents from Amsterdam, the Netherlands, explores emotional responses as an underlying mechanism used to explain residents' behavioral responses as well as their tourism concern as boundary conditions for this mediating effect. In contributing to the extant debate on the role of place attachment (i.e., the bond between people and their environment) in predicting residents' supportive behavior for tourism development, the findings reveal that high levels of place attachment generally result in oppositional behavior. Moreover, results confirm that emotions, as evoked by tourism-induced place change, explain residents' supportive and oppositional responses. Positive emotional responses to tourism decrease the likelihood of residents' oppositional behavior. High levels of tourism concern diminish the positive influence of place attachment on positive emotions.